Microstructure and Optical Properties of BaMO4 (M = Mo, W) Particles Synthesized by Microwave-Assisted Metathetic Method - Atuchin, Victor; Zhu, Lei; Hyun Lee, Soo; Hyun Kim, Dae; Sung Lim, Chang (Asian Journal of Chemistry, 2014)
The BaMO4 (M = Mo, W) particles have been synthesized successfully by a cyclic microwave-assisted metathetic method followed by heat-treatment. Well-crystallized BaMO4 (M = Mo, W) particles with a fine and octahedron-like morphology and the particle size of 1-2 μm have been formed after annealing at 600 ºC for 3 h. The synthesized BaMO4 (M = Mo, W) particles have been characterized by X-ray diffraction and scanning electron microscopy. The optical properties have been investigated by photoluminescence emission and Raman spectroscopy.